PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, COACHING LEADERSHIP, DAN DIGITAL LEADERSHIP KEPALA SEKOLAH TERHADAP KOMPETENSI DIGITAL GURU SMP NEGERI DI KABUPATEN PEMALANG - Tohir; Sitti Hartinah DS; Beni Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the influence of transformational leadership, coaching leadership, and digital leadership on teachers' digital competence in Pemalang Regency. The research uses a quantitative approach with a correlational survey method. Data were collected through questionnaires from a sample of 205 teachers and analyzed using multiple linear regression. The results showed that transformational leadership, coaching leadership, and digital leadership have a significant and positive influence on digital competence. This implies that school leadership plays a key role in enhancing teachers' digital skills.